İntramüsküler benzatin penisilin G enjeksiyonunda manüel basınç uygulamanın enjeksiyon ağrısına etkisinin değerlendirilmesi - Yavuz, Derya Emre (My University, 2011)
1. ÖZET Bu çalışmanın amacı, intramüsküler enjeksiyon öncesi enjeksiyon bölgesine manüel basınç uygulanmasının enjeksiyon ağrısını azaltıp azaltmadığını araştırmaktır. Araştırmada çapraz düzende tek kör olarak olgular kendi içinde karşılaştırıldı. Romatizmal ateşten korunmak için benzatin penisilin G kullanan hastalar çalışmada yer aldı. Üç hafta arayla her bir olgunun bir kalçasına manüel basınçlı diğer kalçasına da basınçsız yöntemle enjeksiyon uygulandı. İki enjeksiyon yöntemi randomize edildi. Ağrı algısı görsel analog ölçeği ile ölçüldü. Çalışmaya 51 hasta dahil edildi. Yirmi dokuz (%56,9)’u kız, 22 (%43.1)’si erkek, tüm olguların yaş ortalaması 15.6 ± 2.9 yıl idi. Manüel basınçlı enjeksiyonunda ağrı algı skoru 1.3 ± 0.9, basınçsız enjeksiyonda 4.4 ± 1.6 bulundu (p<0.001). Manüel basınçlı enjeksiyonla azalan ağrı skor ortalamalarında kız ve erkekler (sırasıyla; 1.4 ± 1.0’e karşın 1.0 ± 0.6) arasında anlamlı fark saptanmadı (p>0.05). Bulgularımız enjeksiyon bölgesine manüel basınç uygulamanın enjeksiyon ağrısını azaltabildiğini ve her iki cinsiyet içinde eşit düzeyde etkili olduğunu göstermektedir. Benzatin penisilin, Hemşirelik, İntramüsküler enjeksiyon, Romatizmal ateş 2.

Effectiveness of the application of manual pressure prior to intramuscular injection to decrease injection pain in children and adolescents with rheumatic fever The purpose of this study was to investigate whether if applying manual pressure to the injection site before intramuscular injection reduces pain. It was a crossover single blind experimental design with intrasubject comparison. The patients who were prescribed benzathine penicillin G injections for the prevention of rheumatic fever were included in the study. Each subject received an injection with manual pressure to one buttock and injection without manual pressure to the other buttock with three weeks interval. Two injection methods were randomly allocated. The perception of pain was measured on a visual analogue scale. Fifty-one patients were recruited into the study. Twenty-nine (56.9%) were female and 22 (43.1%) were male. The mean age was 15.6 ± 2.9 years old. The mean score for perceived pain intensity for the manual pressure injection was 1.3 ± 0.9 and the mean score for the injection without manual pressure was 4.4 ± 1.6 (p<0.001). A significant difference was not found in the perceived pain reduction due to manual pressure between females and males (1.4 ± 1.0 versus 1.0 ± 0.6, respectively; p>0,05). The findings indicate that application of manual pressure to the injection site can decrease injection pain and manual pressure is equally effective for both male and female. Key words: Benzylpenicillin, Intramuscular injection, Nursing, Pain, Rheumatic fever
Keywords: Hemşirelik Esasları